Compositional effects on the hydrogen storage properties in a series of refractory high entropy alloys - Zlotea, Claudia; Bouzidi, Anis; Montero, Jorge; Ek, Gustav; Sahlberg, Martin (Frontiers in Energy Research, 2022)
The possible combinations in the multidimensional space of high entropy alloys are extremely broad which makes the experimental incremental research limited. As a result, establishing trends with well-known empirical parameters (lattice distortion, valence electron concentration etc.) and predicting effects of the chemical composition change are vital to guide future research in the field of materials science. We propose here a strategy to rationalize the effect of chemical composition change on the hydrogen sorption properties in a series of high entropy alloys: Ti0.30V0.25Zr0.10Nb0.25M0.10 high entropy alloys with M = Mg, Al, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo and Ta and a quaternary Ti-V-Zr-Nb pristine material. The maximum hydrogen storage capacity at room temperature strongly depends on the valence electron concentration (VEC) of the alloys: the capacity is high for low values of VEC whereas, a drastic fading is observed for VEC ≥ 4.9. The structural analysis suggests that steric effects might not be responsible for this trend and electronic reasons may be invoked. Increasing the VEC by alloying with late 3d transition metals will fill the unoccupied valence states and the electrons from interstitial hydrogen can no longer be accommodated, which is detrimental for hydrogen storage. Moreover, the onset temperature of desorption increases almost linearly with VEC for this composition series suggesting that alloys with high VEC are less likely to become promising candidates for hydrogen storage.